2003
DOI: 10.1104/pp.103.029587
|View full text |Cite
|
Sign up to set email alerts
|

Blue Light and Phytochrome-Mediated Stomatal Opening in the npq1 and phot1 phot2 Mutants of Arabidopsis

Abstract: Recent studies have shown that blue light-specific stomatal opening is reversed by green light and that far-red light can be used to probe phytochrome-dependent stomatal movements. Here, blue-green reversibility and far-red light were used to probe the stomatal responses of the npq1 mutant and the phot1 phot2 double mutant of Arabidopsis. In plants grown at 50 mol m Ϫ2 s Ϫ1 , red light (photosynthetic)-mediated opening in isolated stomata from wild type (WT) and both mutants saturated at 100 mol m Ϫ2 s Ϫ1 . Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
60
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 22 publications
1
60
1
Order By: Relevance
“…Certainly the presence of five phytochromes, two cryptochromes, two phototropins, and three other LOV domain receptors suggest the plant light sensor collection coordinates a complex circuit of integrated responses that are dependent upon plant developmental state, tissue, or cell type. Add to this the noted and potential light-sensing roles for zeaxanthin (Frechilla et al, 2000;Talbott et al, 2003), cry-DASH (Brudler et al, 2003), G proteins (Warpeha et al, 1991), and possibly flavinbinding aquaporins (Lorenz et al, 2003) and it is clear that there are many additional candidates that may be modulating the GL plastid response. It also is of interest to determine how the developmentally contrary GL effects integrate with the inductive photomorphogenic responses associated with blue and red wavebands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly the presence of five phytochromes, two cryptochromes, two phototropins, and three other LOV domain receptors suggest the plant light sensor collection coordinates a complex circuit of integrated responses that are dependent upon plant developmental state, tissue, or cell type. Add to this the noted and potential light-sensing roles for zeaxanthin (Frechilla et al, 2000;Talbott et al, 2003), cry-DASH (Brudler et al, 2003), G proteins (Warpeha et al, 1991), and possibly flavinbinding aquaporins (Lorenz et al, 2003) and it is clear that there are many additional candidates that may be modulating the GL plastid response. It also is of interest to determine how the developmentally contrary GL effects integrate with the inductive photomorphogenic responses associated with blue and red wavebands.…”
Section: Discussionmentioning
confidence: 99%
“…GL specifically inhibits seedling mass (Went, 1957), plant cell culture growth (Klein, 1964), and elongation during gravitropic stimulation (Klein, 1979) among other responses (Klein, 1992). Contemporary studies have shown that GL can reverse blue and UV-B-induced stomatal opening (Frechilla et al, 2000;Eisinger et al, 2003;Talbott et al, 2003). In all of these cases, the response to GL is in direct opposition to the normal progression of light-mediated processes.…”
mentioning
confidence: 99%
“…This response has been shown to involve the activation of a plasma membrane H 1 -ATPase (Kinoshita and Shimazaki, 1999), although the steps leading up to this activation are not clear. The receptor for this response has yet to be identified unequivocally, and there is evidence supporting both zeaxanthin Talbott et al, 2003) and phototropins Doi et al, 2004) for this role. The RL response is also poorly understood, but many data suggest the involvement of guard cell photosynthetic processes.…”
mentioning
confidence: 99%
“…A blue light photoreceptor for the signal transduction chain in guard cells has been suggested to be the carotenoid pigment zeaxanthin (Zeiger et al 2002;Talbott et al 2003). Phototropin has also been postulated as a blue light photoreceptor (Kinoshita et al 2001).…”
mentioning
confidence: 99%